2003
DOI: 10.3168/jds.s0022-0302(03)73857-0
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Egg as an Alternative Protein Source in Calf Milk Replacers

Abstract: The use of alternative proteins in milk replacer has been evaluated for their ability to decrease the cost of milk replacers without negatively impacting performance of the calf. Three studies were conducted to evaluate the performance of calves fed milk replacer utilizing liquid egg as an alternative protein and to determine the optimal concentration of liquid egg to include in milk replacers. Calves in trials 1 and 2 were assigned to a control diet of all milk protein replacer (MILK) or a diet formulated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…For this reason, egg yolk and whole eggs have been studied extensively as an alternative protein source for animal feeding, with promising results. Most of the authors conclude that when egg is included at levels up to 10 % of the diet (around 30 % of the total protein), growth performance of the calves is improved or similar to that observed when they receive only Ab free milk diets (Touchette et al, 2003). In our work, we supplemented the milk diet of newborn calves with 6.25 % of crude egg yolk (Gp 1 and Gp 2).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…For this reason, egg yolk and whole eggs have been studied extensively as an alternative protein source for animal feeding, with promising results. Most of the authors conclude that when egg is included at levels up to 10 % of the diet (around 30 % of the total protein), growth performance of the calves is improved or similar to that observed when they receive only Ab free milk diets (Touchette et al, 2003). In our work, we supplemented the milk diet of newborn calves with 6.25 % of crude egg yolk (Gp 1 and Gp 2).…”
Section: Discussionmentioning
confidence: 54%
“…Passive protection of newborn calves against Group A BRV using specific egg yolk immunoglobulins as a milk supplement within the immediate postnatal period may be a suitable clinical option to control BRV diarrhea. It has been demonstrated previously that treatment of BRV diarrhea using avian egg yolk enriched in BRV specific IgY Abs during the first 2 weeks of life enhanced body weight gain and markedly reduced BRV infection (virus titer in stools as well as the number of calves shedding virus) (Heckert et al, 1999;Kuroki et al, 1997;Touchette et al, 2003). This indicates that egg yolk Abs can be a potential tool against BRV infection when administered daily immediately after birth, when BRV incidence is higher.…”
Section: Introductionmentioning
confidence: 93%
“…2) Egg proteins were suggested to be an alternative protein source in calf milk replacer because of their low cost and safety as well. 3) Cho et al reported that proteins from hen egg yolk do not contain allergenic proteins or cholesterol. 4) Based on this, this study was planned to examine the functional effects of delipidated egg yolk proteins (YP) on longitudinal bone growth during the growth period.…”
mentioning
confidence: 99%
“…10) Egg proteins have been suggested to be an alternative protein source in calf milk replacer in view of their low cost and safety. 11) In this study, it was found that YSP stimulated the proliferation, differentiation, and mineralization of osteoblasts. In addition, it increased collagen content.…”
mentioning
confidence: 99%